2023
DOI: 10.3390/cells12040587
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Molecular Characterization of Two Patient-Derived Pancreatic Ductal Adenocarcinoma Cell Lines as Preclinical Models for Treatment Response

Abstract: The prognosis of pancreatic ductal adenocarcinoma (PDAC) is exceedingly poor. Although surgical resection is the only curative treatment option, multimodal treatment is of the utmost importance, as only about 20% of tumors are primarily resectable at the time of diagnosis. The choice of chemotherapeutic treatment regimens involving gemcitabine and FOLFIRINOX is currently solely based on the patient’s performance status, but, ideally, it should be based on the tumors’ individual biology. We established two nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Single-cell RNA analyses showed that cells of the basal-like subtype are much more widespread than generally assumed and can also be detected in classical classified pancreatic cancers (10). Moreover, recent studies described single cells expressing both classical and basal markers (11,40). Such co-expressing cells appear to reflect an intermediately differentiated state.…”
Section: Discussionmentioning
confidence: 91%
“…Single-cell RNA analyses showed that cells of the basal-like subtype are much more widespread than generally assumed and can also be detected in classical classified pancreatic cancers (10). Moreover, recent studies described single cells expressing both classical and basal markers (11,40). Such co-expressing cells appear to reflect an intermediately differentiated state.…”
Section: Discussionmentioning
confidence: 91%